Purchase Order Transactions in Islamic Economic Law: A Case Study of PT Segara Artha Investama (PT. SAI) - Afifah, Mutiara Nurzahra; Faizi, Mr. (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2024)
Purpose – This study aims to explore the implementation of Sharia contracts in purchase orders, contributing to the existing literature in the field of the Islamic economy.Method – Employing qualitative research methods with a descriptive research design, the researcher conducted in-depth interviews to gain a comprehensive understanding of purchase order activities. Data analysis was carried out both in the field and through policy analysis. The data analysis technique used was qualitative.Result – The findings of this study indicate that the implementation of purchase orders is in line with Sharia contracts, specifically “Salam” and “ Istishna' ”.Implication –The implications of this research are to offer literature research as a reference for community transactions following Islamic law and to enhance understanding of the concept of transaction contracts in Islamic law.